VALIDITY TEACHING MATERIALS OF INDONESIAN EDUCATION IN BEGINNING CLASS OF ELEMENTARY SCHOOL COURSE BASED INTEGRATED SCIENCE AND SOCIAL STUDIES - Wahyu Sukartiningsih (STKIP Singkawang, 2016)
The aim of the research is to develop teaching materials of Indonesian education in beginning class of elementary school course based integrated science and social studies based Scientific Approach to optimize students competence in Elementary School Teacher Education Department. The specific objective of the first study to explain the validity of teaching materials of Indonesian education in beginning class of elementary school course based integrated science and social studies based Scientific Approach to optimize students competence in Elementary School Teacher Education Department. This study consists of two main steps: Firstly, to design teaching materials refers to the 4-D model of development; Secondly, to explain validity the teaching materials. Data collection techniques is questionaire. The research instrument consisted of Questionaire respon. Data from this study were analyzed by descriptive statistics, such as score of quesionaire Response students and lecturer. The results showed that the teaching materials of Indonesian education in beginning class of elementary school course based integrated science and social studies based Scientific Approach to optimize students competence in Elementary School Teacher Education Department was valid.